2014
DOI: 10.1002/hc.21216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkane Linker Length and Chalcogen Character in [FeFe]‐Hydrogenase Inspired Compounds

Abstract: Models of [FeFe]‐hydrogenases containing diselenolato ligands with different bridge linker length have been prepared: Fe2(μ‐Se(CH2)4Se‐μ)(CO)6 (4DS), and Fe2(μ‐Se(CH2)5Se‐μ)(CO)6 (5DS) as well as dithiolato Fe2(μ‐S(CH2)4S‐μ)(CO)6 (4DT) and compared with Fe2(μ‐S(CH2)3S‐μ)(CO)6 (PDT) and Fe2(μ‐Se(CH2)3Se‐μ)(CO)6 (PDS). Compounds 4DT, PDS, 4DS, and 5DS were characterized by spectroscopic techniques including NMR, IR, mass spectrometry, ultraviolet photoelectron spectroscopy (UPS), elemental analysis, and X‐ray cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Me 3 NOÁ2H 2 O, dppm and dppf were commercially available and used as received. 2-Phenyl-1,3-bis(selenocyanato)propane and Fe 3 (CO) 12 were prepared according to literature protocols [25,26]. Preparative TLC was carried out on glass plates (25 cm 9 20 cm 9 0.25 cm) coated with silica gel G (10-40 lm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Me 3 NOÁ2H 2 O, dppm and dppf were commercially available and used as received. 2-Phenyl-1,3-bis(selenocyanato)propane and Fe 3 (CO) 12 were prepared according to literature protocols [25,26]. Preparative TLC was carried out on glass plates (25 cm 9 20 cm 9 0.25 cm) coated with silica gel G (10-40 lm).…”
Section: Methodsmentioning
confidence: 99%
“…By reaction of 2-phenyl-1,3-dibromopropane with potassium selenocyanate, 2-phenyl-1,3-bis(selenocyanato)propane was readily acquired [29]. As shown in Scheme 1, reaction of 2-phenyl-1,3-bis(selenocyanato)propane with Fe 3 (CO) 12 afforded complex 1. Reaction of complex 1 with dppm in refluxing xylene gave the intra-molecular bridging complex 2.…”
Section: Synthesis and Spectroscopic Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…It is found that the electron density at the Fe centres in these models is increased and hence the protonation of these centres became possible by strong or moderate acids (HBF 4 ⋅Et 2 O, CF 3 CO 2 H; p K a =0.1 and 12.7 in MeCN, respectively). Moreover, we reported different diselenolate mimics having the general formula [Fe 2 (CO) 6 { μ ‐(SeCH 2 ) 2 (CH 2 ) n }] (n=2, 3, 4) with different bridging linker length from the reaction of Fe 3 (CO) 12 with diselenocyanatoalkanes . In the case of n=3 and 4, the reaction produced another compound that contains four iron atoms of the formula [Fe 2 (CO) 6 { μ ‐(SeCH 2 ) 2 (CH 2 ) n }] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The alkyl linker in these complexes forms an agostic interaction with the vacant site on the rotated Fe core. In addition, the reduction potentials of these complexes shift positively by increasing the linker‘s length …”
Section: Introductionmentioning
confidence: 99%